Analisis Perlindungan Hukum Bagi Kesehatan Warga di Kawasan Pemukiman Tempat Pembuangan Akhir Tamangapa - Indar Indar; Nia Astarina Mas’ud; Slamet Sampurno; Nur Azisa; Haeranah Haeranah; Nur Inayah Ismaniar (Media Kesehatan Masyarakat Indonesia, 2019)
This study aims to determine the legal protection for residents’ health in the final disposal area (TPA)Tamangapa and the role of the government in Makassar for ensuring the health of residents around the landfillof Tamangapa TPA. This research was normative and empirical, ie researching secondary data firstly, followedby researching primary data directly in the field. Data were analyzed and presented by descriptive qualitative.The results show that 76% of the residents had been living for over 10 years in Tamangapa TPA and 68% feeldisturbed by the existence of Tamangapa TPA. Although, the health problems are still lacking in the community.The interview results showed that 76% of residents did not feel skin health problems, 64% of residents did not feelrespiratory health problems, 84% of residents did not feel digestive tract health problems and 76% of residents didnot feel other health problems. Regarding the existence of Tamangapa TPA, 56% of the residents suggested thatthe Tamangapa TPA should be moved.